Characterization of medicines discarded at the collection point at a university in northeast Brazil - Paoli Bias Ramos, Sharon; Rodrigues Martins de Freitas, Gabriel; Teresa Lacerda Jales, Silvana (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To characterize the profile of medicines discarded by the university community in the collector made available at the Health Sciences Center of the Federal University of Paraíba. Methods: The Descarta CIM extension project installed a collector in the Medi-cines Information Center - CIM of the Department of Pharmaceutical Sciences. From this, discarded medicines were weighed and cataloged over a period of 6 months, followed by detailed analysis of the type of medicine, regulatory category, ATC (Anatomical The-rapeutic Chemical) classification, pharmaceutical form, type of packaging and expira-tion date. Results: The data found indicates that generic medicines represent 42.5% of the discarded volume, followed by reference medicines (35.7%) and similar medicines (21.7%). Analysis of the ATC classification reveals a prevalence of medications related to the digestive system and metabolism, followed by the cardiovascular system, nervous system and musculoskeletal system. There is a high percentage of medicines that are out of date (72.8%), raising questions about the practice of self-medication and the need to raise awareness about the rational use of medicines. Conclusion: The study has some limitations, especially when it is not possible to determine exactly whether all discarded medications were, in fact, used by members of the university community, their families or people in their social circles. However, the analysis demonstrated that the promotion of educational campaigns and the presence of collectors encourage the proper disposal of medicines and encourage a change in behavior and the practice of environmental protection actions.